G3 2012 Progress Report: Water Governance and Community Based Management - CGIAR Challenge Program on Water and Food (2012)
The Ganges Basin Development Challenge (GBDC) commissioned by the CPWF, aims to increase resilience of agricultural and aquaculture systems in the Ganges delta focusing water and food security. There are five projects namely G1, G2, G3, G4 and G5 having different objectives under Ganges Basin Development Challenge (BDC) program. The Project G3 is titled “Water governance and community based management”. The International Water Management Institute (IWMI) is the lead institute for the G3 research project and is responsible for coordinating all research activities under G3 and its partners with the aim to produce high quality research outputs. Inundation, salinity intrusion and severe flooding in the coastal areas are frequent occurrences in Bangladesh. This leads to loss of life and property as well as severe impacts on livelihoods. The government of Bangladesh has invested steadily in coastal zone management through construction and rehabilitation of polders. Involvement of communities in management of polders is now enshrined in Bangladesh’s Water Policy. This project tries to understand various aspects of water governance and communities based management of polders in coastal zones in Bangladesh and then suggest implementable policy options for improving polder governance in Bangladesh.